Here or here? A sociolinguistic study - Quintanilla Anglas, Rómulo (2003)
The adverbs “acá” and “aquí” are regarded by the Royal Academy of the Spanish Language and the grammarians, this are trend as synonyms, that is, the use of either one would depend on the preference of the user. In our environment, the seem to be different semantically but it do not depend on the user's style. “Acá” is an adverb which semantically restricts its meaning pointing out a narrower environment and a broader vecinity to the speaker. “Aquí” expresses not only the concept of a longer distance in relation to the speaker but also a broader environment.